Genetic Polymorphisms and the Clinical Response to Systemic Lupus Erythematosus Treatment Towards Personalized Medicine - Barliana, Melisa Intan; Afifah, Nadiya Nurul; Amalia, Riezki; Hamijoyo, Laniyati; Abdulah, Rizky (Frontiers in Pharmacology, 2022)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by a broad spectrum of clinical manifestations, an aberrant autoimmune response to self-antigens, which affect organs and tissues. There are several immune-pathogenic pathways, but the exact one is still not well known unless it is related to genetics. SLE and other autoimmune diseases are known to be inseparable from genetic factors, not only pathogenesis but also regarding the response to therapy. Seventy-one human studies published in the last ten years were collected. Research communications, thesis publication, reviews, expert opinions, and unrelated studies were excluded. Finally, 32 articles were included. A polymorphism that occurs on the genes related to drugs pharmacokinetic, such as CYP, OATP, ABC Transporter, UGT, GST or drug-target pharmacodynamics, such as FCGR, TLR, and BAFF, can change the level of gene expression or its activity, thereby causing a variation on the clinical response of the drugs. A study that summarizes gene polymorphisms influencing the response to SLE therapy is urgently needed for personalized medicine practices. Personalized medicine is an effort to provide individual therapy based on genetic profiles, and it gives better and more effective treatments for SLE and other autoimmune disease patients.